Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1017/s0952836900006038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temporal and spatial variations in food supply on the space and habitat use of red squirrels (Sciurus vulgaris L.)

Abstract: In non-native conifer plantations characterized by strong spatial and temporal variations in the availability of tree seeds in Spadeadam Forest, northern England, the home range and habitat use of red squirrels Sciurus vulgaris was very¯exible. Males tended to have much larger home ranges than females and coreareas of most breeding females seemed mutually exclusive. Adult female red squirrels were found to increase their home range and core-area size in forest patches where food was less abundant. Home-range s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 25 publications
1
53
1
Order By: Relevance
“…Finally, the animal's relatively large body size, diurnal habits and average lifetime allow detailed analysis of their lifehistory traits and social organization (Wauters & Dhondt 1989, 1992, 1995Lurz et al . 1997Lurz et al . , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the animal's relatively large body size, diurnal habits and average lifetime allow detailed analysis of their lifehistory traits and social organization (Wauters & Dhondt 1989, 1992, 1995Lurz et al . 1997Lurz et al . , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, like other rodent species with scramble competition mating systems (Koprowski 2007;Lane et al 2009;Raveh et al 2010;Marmet et al 2012), only those males that can locate estrous females faster than other male competitors should be favored by sexual selection, as female tree squirrels are commonly in estrus for <1 d and likely <8 h (Koprowski 2007). Mearns's squirrels exhibited intra-and intersexual overlap in 95% FK home ranges year round similar to scatter-hoarding rodents (Frank & Heske 1992;Lurz et al 2000;Shier & Randall 2004;Cudworth & Koprowski 2010), including red squirrels in deciduous forests (Layne 1954;Kemp & Keith 1970;Don 1983;Gurnell 1984). Nonetheless, overlap only differed between seasons suggesting that overlap is similar for both sexes within seasons, with lower and higher overlap during non-mating and mating seasons, respectively, between sexes.…”
Section: Discussionmentioning
confidence: 83%
“…An increase in overlap during mating season between female Mearns's squirrels may be due to habitat heterogeneity with females searching more widely for food, but covering areas of similar size as those traveled during non-mating season. In Eurasian red squirrels and root voles (Microtus oeconomus), higher overlap between females only occurs when food supply declines and consequently energy requirements increase, particularly during mating season (Lurz et al 2000;Hoset et al 2008). Mearns's squirrels also rely on tree cavities for nesting (Ramos-Lara et al 2013), and both sexes were observed frequently inspecting tree cavities which also may have contributed to increased overlap with other conspecifics, particularly breeding females (Peterson & Gauthier 1985;Hanski et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Space use integrates complex behavioral decisions that include intra-and inter-specific competition (Davis et al 2017); antipredator strategy (Thaker et al 2011, Palmer et al 2017; quality, quantity, and configuration of resources (Lurz et al 2000, Marzluff et al 2004; and social structure (Fortin et al 2009, Lesmerises et al 2018a). Consequently, space use can have important impacts on individual survival or recruitment (Brinkman et al 2004, Lafontaine et al 2017.…”
Section: Introductionmentioning
confidence: 99%